THE PERCEPTION OF PHYSICAL EDUCATION IN THE ROMANIAN EDUCATIONAL SYSTEM - P. C. MOISESCU; R. M. BURLUI (Editura Universitatii Transilvania din Brasov, 2019)
School physical education not only contributes to a good physical condition and health of students, but also helps them better understand physical activity and positive repercussions for their entire lives. Moreover, School Physical Education determines the transfer of knowledge and skills as a team spirit and fair play, cultivates respect, social awareness and self, provides a general understanding of the "rules of the game", which students can use then more promptly to other school subjects or life situations.